Profiling of carotenoid pigments and their antioxidant activities in ray florets of chrysanthemum (Chrysanthemum × morifolium) - SHISA ULLAS P; NAMITA NAMITA; KANWAR P SINGH; ADITI KUNDU; SAPNA PANWAR; GOPALA KRISHNAN S; GUNJEET KUMAR (The Indian Journal of Agricultural Sciences, 2023)
In present study, different varieties of chrysanthemum (Chrysanthemum × morifolium Ramat) were screened for total carotenoids, phenolic content and antioxidant activities. Among the genotypes studied, variety Jubilee (32.82 mg/100g) exhibited high total carotenoids followed by varieties Haldighati (26.71 mg/100 g), Little Orange (22.25 mg/100g), Liliput (20.77 mg/100g) and Star Yellow (19.21 mg/100g). Variety Jubilee also showed highest antioxidant activities of carotenoids {CUPRAC-Cupric reducing antioxidant capacity (149.44 μmol trolox/g), FRAP- Ferrous reducing power (40.09 %), DPPH radical scavenging activity (11.24%)}. The total phenolic content varied from 1.26 mg GAE/g (Ram Lal Dada) to 31.14 mg GAE/g (Jubilee) on fresh weight basis. Further, five promising varieties having high carotenoids, were quantified for lutein and β-carotene using High Performance Liquid Chromatography (HPLC). Highest lutein content was found in variety Jubilee (19.90 μg/g) followed by varieties Haldighati (8.67 μg /g), Liliput (4.77 μg /g), Star Yellow (3.93 μg /g) and Little Orange (3.69 μg/g). Highest β-carotene content was found in Little Orange (5.51μg/g) followed by the varieties Haldighati (2.04 μg /g), Jubilee (1.77 μg /g), Liliput (0.54 μg /g) and Star Yellow (0.50 μg/g). A high correlation between carotenoids, total phenolic and antioxidant activities was observed. Variety Sadwin Yellow showed highest total carotenoid (0.48 mg/g) in leaves, whereas chlorophyll a and total chlorophyll was highest in variety Punjab Anmol (1.32 mg/g, 1.56 mg/g) and high chlorophyll b in variety Pusa Aditya (0.28 mg/g).